Postmodernism, Literature and the Future of Theology
IX, 194 p.
Keywords: These essays are written by scholars from widely differing disciplines and traditions. Theologians, philosophers, literary critics and historians of ideas approach the question of how the judaeo-Christian tradition of theological reflection has suffered from and will negotiate the emergence of postmodern theory and practice in literature and criticism. Chapters deal with specific texts from Euripides to contemporary fiction, and with the traditions of cultural theory from Nietszche to Benjamin, to Derrida and what David Klemm identifies as the tragedy of present theology.